Distribution System Power Losses Minimization Using Network Reconfiguration - Tahir, Muhammad Junaid; Abu Bakar, Badri; Alam, Muhammad; Mazliham, MS (International Journal of Integrated Engineering, 2018)
This paper shows an efficacious approach for the perfect arrangement of a distribution system. To discover the switches best fusion, which outcomes a minimal power loss for the distribution radial configuration. To resolve the non-linear optimization problem here Modified Particle Swarm Optimization (MPSO) technique is projected for the minimization of system power losses. MPSO is an improved Binary Particle Swarm Optimization (BPSO) with modification of particle velocity in search space. To reveal the fitness of the anticipated approach relative investigation of MPSO with other preceding optimization techniques is done. To reconfigure a distribution network system, under base case loading conditions, IEEE 33 bus radial system is used. It is inspected that MPSO executes well as compare to GA, ACA and SPSO in respective of significance of power losses, which are improved and minimized up to 138.9275kW and profile of voltage, which are enhanced and stabilized up to 0.94234 per unit in terms of minimum voltage in the system.